Global mesothelioma deaths reported to the World Health Organization between 1994 and 2008 - Vanya Delgermaa; Ken Takahashi; Eun-Kee Park; Giang Vinh Le; Toshiyuki Hara; Tom Sorahan (Bulletin of the World Health Organization, 2011)
OBJECTIVE: To carry out a descriptive analysis of mesothelioma deaths reported worldwide between 1994 and 2008. METHODS: We extracted data on mesothelioma deaths reported to the World Health Organization mortality database since 1994, when the disease was first recorded. We also sought information from other English-language sources. Crude and age-adjusted mortality rates were calculated and mortality trends were assessed from the annual percentage change in the age-adjusted mortality rate. FINDINGS: In total, 92 253 mesothelioma deaths were reported by 83 countries. Crude and age-adjusted mortality rates were 6.2 and 4.9 per million population, respectively. The age-adjusted mortality rate increased by 5.37% per year and consequently more than doubled during the study period.The mean age at death was 70 years and the male-to-female ratio was 3.6:1.The disease distribution by anatomical site was: pleura, 41.3%; peritoneum, 4.5%; pericardium, 0.3%; and unspecified sites, 43.1%.The geographical distribution of deaths was skewed towards high-income countries: the United States of America reported the highest number, while over 50% of all deaths occurred in Europe. In contrast, less than 12% occurred in middle- and low-income countries. The overall trend in the age-adjusted mortality rate was increasing in Europe and Japan but decreasing in the United States. CONCLUSION: The number of mesothelioma deaths reported and the number of countries reporting deaths increased during the study period, probably due to better disease recognition and an increase in incidence. The different time trends observed between countries may be an early indication that the disease burden is slowly shifting towards those that have used asbestos more recently.